Filmmakers and financing : business plans for independents. - Levison, Louise, ....- (Oxford : Focal, 2007)
The first, most crucial step in making a film is finding the funds to do it. Let Louise Levison, who wrote the innovative business plan for "The Blair Witch Project," show you how. Whether you're planning a feature, short, documentary, or large format film, this unique guide teaches you how to create a business plan that can be presented to a potential investor. In jargon-free terms, the author leads you through every step. Each chapter concentrates on a different section of the business plan, including the industry, marketing, financing, distribution. There are supplementary exercises and spreadsheets on the CD workbook so you get comfortable crunching the numbers--no math degree required! The fifth edition contains completely revised and updated industry data, updated information on the market for short films, as well as a new chapter on nontraditional films such as documentaries. * Includes a CD workbook with forms, spreadsheets, and hands-on exercises * A sample business plan is included as a helpful reference * Learn how to develop business plans for features, shorts, documentaries and more Contents Executive Summary The Company The Films The Industry The Markets and Marketing The Markets Part 2: The Nontraditional Film Distribution Risk Factors Financing The Financial Plan Sample Business Plan Short Film Distribution
Keywords: Business plans; Film; Marketing -- Filmindustrie